Effectiveness of RL preload hydration in preventing hypotension in post-spinal anesthesia patients - Irwadi, Irwadi; Saputra, Andre Utama (International Journal of Health Science and Technology, 2024)
Hypotension often occurs in spinal anesthesia patients due to suppression of the autonomic nervous system, specifically the sympathetic nerve, leading to vasodilation. This study aims to evaluate the effectiveness of preloading RL in preventing hypotension. The design uses a quasi-experiment with a pretest-posttest design with a control group. A total of 50 respondents were selected by purposive sampling and divided into intervention and control groups. Blood pressure data was measured using a NIBP monitor and recorded on an observation sheet. The results showed that the average systolic and diastolic pressure in the intervention group was 125.20 mmHg and 81.24 mmHg, in the control group was 115.20 mmHg and 70.57 mmHg. The paired sample t-test showed a significant difference (p < 0.05). Preload RL is effective in preventing hypotension in spinal anesthesia.